Adding to the complexity of fetal and neonatal alloimmune thrombocytopenia: Reduced fibrinogen binding in the presence of anti-HPA-1a antibody and hypo-responsive neonatal platelets. Issue 162 (February 2018) - Refsum, E.; Meinke, S.; Gryfelt, G.; Wikman, A.; Höglund, P.
Abstract: Background: In fetal and neonatal alloimmune thrombocytopenia (FNAIT), maternal alloantibodies directed against paternally-derived platelet antigens are transported across the placenta to the fetus, where they may cause thrombocytopenia. The most serious complication of FNAIT is an intracranial hemorrhage (ICH), which may cause death or life-long disability of the child. Apart from alloantibody-mediated platelet destruction, the clinical outcome in FNAIT may be affected by properties of neonatal platelets and possible functional effects on platelets caused by maternal alloantibodies. Methods and results: The function of umbilical cord blood platelets was compared with adult platelets in two assays, impedance aggregometry (Multiplate) and rotational thromboelastometry (Rotem). Both revealed a decreased in vitro neonatal platelet function compared to adult platelets. Consistent with this finding, activation using TRAP revealed less pronounced changes in the expression of CD62P, PAC-1, CD41 and CD42a in umbilical cord blood platelets compared to adult platelets. Furthermore, a monoclonal anti-HPA-1a antibody, derived from an immunized mother of two children with FNAIT, blocked fibrinogen binding to resting and activated umbilical cord blood and adult HPA-1aa and HPA-1ab platelets, interfered with platelet activation by TRAP, and impaired the function of umbilical cord blood HPA-1aa platelets in rotational thromboelastometry. Discussion and conclusions: Reduced fibrinogen binding in the presence of anti-HPA-1a antibodies may disturb the neonatal hemostatic balance, characterized by poorly responsive platelets. This effect may operate in parallel to platelet destruction and contribute to the clinical outcome in FNAIT. Highlights: Neonatal platelets exhibit hypo-reactivity compared to adult platelets. Monoclonal anti-HPA-1a reduces fibrinogen binding to HPA-1a positive platelets. Anti-HPA-1a antibodies may affect a decreased neonatal platelet function.